Lexicon Pintar In Indonesian: A Study Of Natural Semantic Metalanguage - Ayu Pujiyani, Ni Putu (International Seminar on Austronesian Languages and Literature, 2021)
This study is aimed to look at the structure and meaning components of knowledge-type state verbs in Indonesian. The data analysed in this study are the  pintar , pandai , cerdas, cermat, cakap, cerdik, mahir, dan terampil . These lexicons were chosen because in the The Great Indonesian Dictionary or Kamus Besar Bahasa Indonesia (KBBI) it was found that the eight lexicons had vague and rotating meanings, making them very interesting for further analysis.  To analyse the data, the method of reading notes and reviewing the literature was used, which was then presented descriptively. The results found in this study are that  pintar , pandai , cerdas, cermat, cakap, cerdik, mahir, dan terampil have almost the same structure and semantic components. The difference lies in the level of ability or knowledge contained in each of these lexicons.